Financial markets in the BOF4 model of the Finnish economy - Juha Tarkka; Alpo Willman (Bank of Finland, 1990)
This paper describes the modelling of financial markets and the balance of payments in BOF4, a quarterly macroeconomic model developed by the Bank of Finland. The short-term interest rate is determined as a result of the interaction of the demand for money and money supply, as in the conventional IS-LM approach. Alternatively, the model may be solved under the assumption that monetary policy is based on pegging interest rates. In that case, the domestic credit of the Central Bank is the equilibrating variable.
URN:NBN:fi:bof-201807311788
Keywords: 330